Understanding the Gender Digital Divide in South Asia: A Qualitative Meta-Synthesis - Ullah, Azmat; Shah, Muhammad Shafqat Ali (Pedagogy and Psychology of Sport, 2026)
This study examines the structural, socio-cultural, and economic factors that shape the gender digital divide across South Asia. Drawing on a qualitative meta-synthesis of regional reports, scholarly literature, and international organizational documents published between 2013 and 2025, the research highlights how patriarchal norms, mobility restrictions, unequal access to ICT resources, limited digital skills, and disparities in educational and economic opportunities collectively restrict women’s participation in the digital environment. The findings reveal that digital inequality is not merely a technological issue but a reflection of deeper social and institutional barriers that marginalize women and impede their involvement in academic, economic, and online spaces. Although digital technologies hold significant potential to enhance women’s empowerment, their benefits remain unevenly distributed due to cultural constraints, limited infrastructure, and policy gaps. The study concludes that addressing the gender digital divide requires gender-responsive ICT policies, community-level awareness, equitable digital education, improved access to devices and internet services, and collaborative efforts among governments, educational institutions, and international organizations. Strengthening women’s digital capabilities is essential to ensuring inclusive development and meaningful participation in the rapidly evolving digital economy.